Parental drinking and adverse outcomes in children: A scoping review of cohort studies. (31st August 2015) - Rossow, Ingeborg; Felix, Lambert; Keating, Patrick; McCambridge, Jim
Abstract: Introduction and Aims: There is a growing interest in measuring alcohol's harms to people other than the drinker themselves. 'Children of alcoholics' and foetal alcohol spectrum disorder have received widespread attention. Less is known about how children are affected by post‐natal exposure to parental drinking other than alcohol abuse/dependence. In this scoping review, we aim to assemble and map existing evidence from cohort studies on the consequences of parental alcohol use for children, and to identify limitations and gaps in this literature. Design and Methods: Systematic review methods were used. Electronic databases were searched (1980 to October 2013) and a total of 3215 abstracts were screened, 326 full text papers examined and 99 eligible for inclusion according to selection criteria including separation of exposure and outcome measurement in time and report of a quantitative effect size. Results: The main finding is the large literature available. Adolescent drinking behaviour was the most common outcome measure and outcomes other than substance use were rarely analysed. In almost two of every three published associations, parental drinking was found to be statistically significantly associated with a child harm outcome measure. Several limitations in the literature are noted regarding its potential to address a possible causal role of parental drinking in children's adverse outcomes. Discussion and Conclusions: This study identifies targets for further study and provides a platform for more targeted analytic investigations which ascertain risk of bias, and which are capable of considering the appropriateness of causal inferences for the observed associations. [Rossow I, Felix L, Keating P, McCambridge J. Parental drinking and adverse outcomes in children: A scoping review of cohort studies. Drug Alcohol Rev 2016;35:397–405]